1983
DOI: 10.1139/e83-105
|View full text |Cite
|
Sign up to set email alerts
|

Remote acoustic classification of marine sediments with application to offshore Newfoundland

Abstract: Shallow marine sediments can be remotely classified by the spatial correlation properties of their seismic reflection signatures provided one uses a highly repetitive broadband acoustic source. A classification scheme defined by three spatial coherence parameters is shown capable of automatically differentiating between several formations of unconsolidated sediments in a limited area of offshore Newfoundland. The consistency and generality of the technique are explored and comparisons with standard echograrn i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Forsgren et al (1993) used the acoustic signal patterns of the echogram to differentiate between fine-and coarse-grained sediment bottoms according to four criteria: roughness of the line surface, line thickness, occurrence of white line and echo. Investigations by Clay and Leong (1974), Dunsinger et al (1981) and Cochrane and Dunsinger (1983) showed that inhomogenities in the sediment cause scattering of acoustic signals. They also showed that with increased roughness of the sediment surface the scattering component of the acoustic signals increased.…”
Section: Bottom Sedimentsmentioning
confidence: 99%
“…Forsgren et al (1993) used the acoustic signal patterns of the echogram to differentiate between fine-and coarse-grained sediment bottoms according to four criteria: roughness of the line surface, line thickness, occurrence of white line and echo. Investigations by Clay and Leong (1974), Dunsinger et al (1981) and Cochrane and Dunsinger (1983) showed that inhomogenities in the sediment cause scattering of acoustic signals. They also showed that with increased roughness of the sediment surface the scattering component of the acoustic signals increased.…”
Section: Bottom Sedimentsmentioning
confidence: 99%